Exchange Rate Bands of Inaction and Play-Hysteresis in German Exports – Sectoral Evidence for Some OECD Destinations - Ansgar Belke; Matthias Goecke; Martin Guenther (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
A non-linear model is applied where suddenly strong spurts of exports occur when changes of the exchange rate go beyond a zone of inaction. We call the latter a 'play' area - analogous to mechanical play and implement an algorithm describing path-dependent play-hysteresis into a regression framework. The hysteretic impact of real exchange rates on German exports is then estimated based on quarterly data from 1995Q1 to 2010Q3. For some of the main export partners of Germany outside the euro area and some of the most important tradable sectors we fi nd significant hysteretic effects for a part of the German exports. – – Ein nicht-lineares Modell wird angewendet, in dem plötzliche starke Reaktionen der Exporte auftreten, sobald eine Inaktivitätszone des realen Wechselkures überschritten wird. Analog zum mechanischen Spiel wird dieses Phänomen eines pfadabhängigen Inaktivitätsbandes 'play' genannt. Mittels eines Algorithmus wird die Play-Hysterese in einen ökonometrischen Schätzansatz implementiert. Für Quartalsdaten deutscher Exporte in wichtige Nicht-Euro-Empfängerländer im Zeitraum von 1995Q1 bis 2010Q3 finden wir für verschiedene deutsche Exportsektoren signifikante hysteretische Play-Effekte.
Keywords: F14; C51; 330; Exchange rate movements; play-hysteresis; modelling techniques; switching/spline regression; export demand